Precision Medicine for Breath-Focused Mind-Body Therapies for Stress and Anxiety: Are We Ready Yet? - Helen Lavretsky MD, MS; Jack L Feldman PhD (SAGE Publishing, 2021)
In this viewpoint, we present an argument for transdisciplinary "precision medicine" approaches that combine studies of basic neurobiology of breathing in animal and human models of stress that can help characterize physiological and neural biomarkers and mechanisms of breathing control and emotion regulation in humans. Such mechanistic research is fundamental for the development of more effective and mechanism-based mind-body therapies. The potential for this research to positively impact public health is high, as breathing techniques are inexpensive, accessible, and cross-culturally accepted, with fewer complications then observed with other standard therapies for stress-related disorders.